(untitled) (Ius Novum, 2023)
The aim of the article is to interpret the conditions for and the content of a claim for an appropriate disability pension granted due to the reduction of prospects for success in the future (the so-called third disability pension condition under Article 444 § 2 of the Civil Code). The choice of the subject of analysis is justified primarily by the fact that in the legal literature this disability pension has been given much less attention than pensions granted due to other conditions specified in Article 444 § 2 CC. The authors focus on solving some of the interpretative doubts emerging in the civil law in relation to the expression: “reduction of the prospects for success in the future”. To carry out the analyses, the derivative conception of interpretation is used. The article shows that a claim for a pension due to the reduction of prospects for success in the future is available to every natural person (including a conceived child) who has suffered such a kind of bodily injury or health disorder that makes them lose the ability to work (within the broad meaning of the word), including the ability to perform household chores and, consequently, the material or financial benefits that this work would bring. The role of the provision, according to the authors, seems to be to resolve interpretation related doubts with regard to the pecuniary benefits that the aggrieved party would obtain in the future with a probability higher than low, small, but lower than the probability bordering on certainty (or at least very high), which is usually required in relation to lost benefits in order to grant a disability pension. This result of the interpretation is fully justified in both systemic and functional interpretative directives.